2020
DOI: 10.7759/cureus.11180
|View full text |Cite
|
Sign up to set email alerts
|

Is Estrogen a Curse or a Blessing in Disguise? Role of Estrogen in Gastroesophageal Reflux Disease

Abstract: Gastroesophageal reflux disease (GERD), a condition wherein there is reflux of stomach contents into the esophagus, causing heartburn and regurgitation with a sour and bitter taste in the mouth. It may or may not lead to mucosal injury. GERD symptoms can be troublesome and negatively impact the quality of life. Estrogen, the sex hormone in females, may play a role in the gender differences observed in GERD symptoms. This review article analyzes estrogen's mechanism in the causation of GERD symptoms and its com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…For example, the use of estrogen plus a progestogen resulted in a significant reduction in LES pressure in women 20 . Previous investigations suggested that nitric oxide acts as a mediator between estrogen and GERD 11,19-21 . The use of estrogens in postmenopausal women is associated with higher plasma nitric oxide levels, and nitric oxide is a key neurotransmitter for relaxation of LES 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the use of estrogen plus a progestogen resulted in a significant reduction in LES pressure in women 20 . Previous investigations suggested that nitric oxide acts as a mediator between estrogen and GERD 11,19-21 . The use of estrogens in postmenopausal women is associated with higher plasma nitric oxide levels, and nitric oxide is a key neurotransmitter for relaxation of LES 22 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Previous investigations suggested that nitric oxide acts as a mediator between estrogen and GERD. 11,[19][20][21] The use of estrogens in postmenopausal women is associated with higher plasma nitric oxide levels, and nitric oxide is a key neurotransmitter for relaxation of LES. 22 In addition, nitric oxide is also associated with temporary relaxation of the LES, one of the key processes behind GERD in patients with reflux esophagitis.…”
Section: Association Of Ht Use With Gerdmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have shown that estrogen could protect the mucosa from GERD injury. This matter still needs further analysis (Kang, Khokale, Awolumate, Fayyaz, & Cancarevic, 2020;Zia & Heitkemper, 2016).…”
Section: Demographymentioning
confidence: 99%